Occurrence and characterization of extended‐spectrum cephalosporin‐resistantEnterobacteriaceaein healthy household dogs in Greece. Issue 7 (July 2018) - Liakopoulos, Apostolos; Betts, Jonathan; La Ragione, Roberto; van Essen‐Zandbergen, Alieda; Ceccarelli, Daniela; Petinaki, Efthymia; Koutinas, Christos K.; Mevius, Dik J.
Abstract : N/A: Extended‐spectrum cephalosporin‐ and/or carbapenem‐resistant (ESC R and/or Carb R ) Enterobacteriaceae constitute a public health hazard because of limited treatment options and are endemic among humans in Greece. Recently, ESC R and Carb R Enterobacteriaceae have been increasingly isolated from companion animals, stressing their potential role as a reservoir for humans. However, the presence of ESC R bacteria in companion animals within Greek households has not been determined yet. Genes conferring the ESC R and Carb R phenotype were detected among canine isolates and their chromosomal or plasmid location was determined. Standard methods were applied for plasmid characterization. The clonal relatedness of the recovered isolates was examined by multilocus sequence typing (MLST). Here, we report the first findings on the presence of ESC R Enterobacteriaceae in healthy Greek dogs. ESC R Escherichia coli isolates were associated with different sequence types (STs), including the human pandemic ST131 clone. The occurrence of human‐related ESBL/pAmpC genes, plasmid types and/or strain STS in this animal reservoir suggests possible bilateral transmission.